Analisis Perbandingan Sistem Pasar Modal dan Pasar Uang Negara Indonesia dan Negara Turki: Perspektif Regulasi Syariah, Stabilitas Keuangan, dan Pertumbuhan Investasi - Ira Damayanti Harahap; Maryam Batubara (CV. ALIM'SPUBLISHING, 2026)
This study aims to analyze the comparison between the capital market and money market systems in Indonesia and Turkey from the perspective of Sharia regulation, financial stability, and investment growth. This research employs a qualitative approach using a comparative study based on literature review and secondary data obtained from financial reports, regulatory policies, and official publications from both countries. The findings indicate that Indonesia has a more structured Islamic financial system supported by strong regulatory frameworks through the Financial Services Authority (OJK) and the National Sharia Board, while Turkey is still in the process of developing broader integration of Islamic finance within its financial system. In terms of financial stability, both countries demonstrate relatively strong resilience, although they remain influenced by global macroeconomic conditions. Meanwhile, investment growth in Indonesia tends to be more stable due to a diversified range of Islamic financial instruments, whereas Turkey shows significant growth potential driven by ongoing financial policy reforms. This study is expected to serve as a reference for strengthening Islamic-based financial systems in both countries.